ANALYZING MATHEMATIC METHODS OF CONTROL OVER POLLUTING MATTERS IMPACT ON THE ENVIRONMENT - Alina M. Minitaeva (Plekhanov Russian University of Economics, 2017)
The article provides the analysis of effective methods to calculate the amount of products of diesel fuel burning. The most promising method was shown, in spite of its labour-consuming nature. The given methodology can allow us: firstly, to reject the results of tests, as their results show only a special case of an individual diesel work; secondly, to calculate the amount of products of burning for any type of diesel and thirdly, to investigate the impact of diesel thermal process parameters on the product range and amount of products of burning. Application of the model could provide an opportunity to choose the condition of engine work, which will exhaust the minimum amount of harmful blow-outs.